PROFIL PENINGKATAN KEMAMPUAN LITERASI KIMIA SISWA MELALUI PEMBELAJARAN INKUIRI TERBIMBING BERBASIS KONTEKSTUAL - Anggraeni, Aas Yanuar; Wardani, Sri; Hidayah, Aidat Nurul (Universitas Negeri Semarang, 2020)
Learing process in classroom in this time directing the students to develop their thinking skills, one of which is chemical literacy ability. Chemical literacy ability can be built by implementing learning activities get used to thinking and develop student knowledge concepts independently. The purpose of this research is to describe the profile of students’s chemical literacy ability improvement through contextual inquiry-based learning. The method used is experimental method with pretest-posttest control group design. Samples were taken using cluster random sampling technique, sample using two classes in X MIPA SMA Islam Sudirman Ambarawa. Data collection method in this research is chemical literacy test and questionnaire. Analysis of data using n-gain test, normality test, similarity two variance test, and t test. The results of the research showed the average value of chemical literacy posttest experimental class 72.86 and control class of 63.42. The test result of n-gain experimental class 0.621 and control class 0.618, both in medium category. The t test results on the posttest value tcount of 3.66 over ttable of 2.00, which means the chemical literacy ability of experimental class is better than control class. Based on these results, it can be concluded that contextual-guided inquiry learning can improve students’s chemical literacy profile on context aspect, knowledge, competency, and attitude aspect.